2009
DOI: 10.1002/ejoc.200900093
|View full text |Cite
|
Sign up to set email alerts
|

Photolabile Carbonyl Protecting Group: A New Tool for Light‐Controlled Release of Anticancer Agents

Abstract: A new type of photolabile carbonyl-protecting group was utilized in releasing anticancer agents upon irradiation at 350 nm in an aqueous environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Wang and co-workers developed a photoremovable protecting group for carbonyl compounds based on trityl photochemistry. 320 Ketones and aldehydes are converted into cyclic acetals ( 173 ) by treatment with 5-methoxysalicylic alcohol derivatives (Scheme 69). Upon irradiation, the carbonyl compounds are released in 75–90% yield and good quantum efficiency ( Φ = 0.11).…”
Section: Arylmethyl Groupsmentioning
confidence: 99%
“…Wang and co-workers developed a photoremovable protecting group for carbonyl compounds based on trityl photochemistry. 320 Ketones and aldehydes are converted into cyclic acetals ( 173 ) by treatment with 5-methoxysalicylic alcohol derivatives (Scheme 69). Upon irradiation, the carbonyl compounds are released in 75–90% yield and good quantum efficiency ( Φ = 0.11).…”
Section: Arylmethyl Groupsmentioning
confidence: 99%
“…These PPGs have advantageous features, including (1) their structural simplicity and chemical stability, (2) simple and cost-effective preparation, (3) high efficiency of protection/deprotection, (4) compatibility with ambient conditions (e.g., air and water) during irradiation, and (5) flexible structural modification without compromising photochemical properties, etc. [5][6][7][8][9][10][11]13,14,16 For applications of these PPGs in aqueous solution as photocages, we demonstrated that by incorporating poly(ethylene glycol) 8 or carboxylate side chains, 16 the PPGs can be converted to their corresponding water-soluble counterpart. For instance, the hydrophobic 3-dimethylaminotrityl group (DMATr) PPG for the hydroxyl group was converted to its water-soluble version (as one shown in 1, Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have recently developed a series of structurally simple PPGs for releasing carbonyl, 5−12 hydroxyl, 12−17 diol, 18 carboxyl, 15 and amino groups. 19,20 Their applications in organic synthesis, 21 photoactivated prodrugs, 8,22 photorelease of perfumes in solid phase, 23 photocleavage of polymers, 12 light-controlled hydrogel formation, 24 and surface patterning 25 have been explored recently. These PPGs have advantageous features, including (1) their structural simplicity and chemical stability, (2) simple and cost-effective preparation, (3) high efficiency of protection/deprotection, (4) compatibility with ambient conditions (e.g., air and water) during irradiation, and (5) flexible structural modification without compromising photochemical properties, etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have recently developed a series of novel PPGs for protection of carbonyl and hydroxyl groups (Scheme 1). [22][23][24][25][26][27][28][29][30][31] For example, a carbonyl compound (1) can be protected by our new PPG reagent 2 and be converted to an acetal/ketal (3), and an alcohol (4) can be protected as an ether by the new PPG reagent 5. Upon UV irradiation, the acetal/ketal 3 and the ether 6 release the carbonyl compound and the alcohol, respectively.…”
mentioning
confidence: 99%
“…A three-step sequence of esterification, acetylation, and Grignard reaction provided the salicyl alcohol 8. 24 Its reaction with the aldehyde 9 under the neutral reaction conditions and the subsequent reduction of the amide moiety led to the known acetal 10 in 84% yield (two steps). Treatment of 10 with propargyl bromide followed by 2-bromo-2-methylpropanoyl bromide resulted in the photolinker 11a in 89% yield (two steps).…”
mentioning
confidence: 99%